Management of the total glossectomy defect with latissimus dorsi free flap - M. M. Davudov; Ch. R. Rahimov; A. A. Akhundov; F. G. Irannezhat; Sh. A. Magomedov; M. Ch. Rahimli; D. A. Safarov (Опухоли головы и шеи, 2018)
Radical surgical management of tongue cancer results in sever speech and swallowing disruption, impaired airway protection and life-threatening aspiration. Surgical objective of total glossectomy defect management is an adequate restoration of lingual mass and affected tissues   of the floor of the mouth. Range of flaps are known to provide the adequate outcome, i. e. pediculed pectoralis major flap, anterolateral free thigh flap, rectus abdominis flap, radial free forearm flap and latissimus dorsi flap.In the current report, we present a case of glossectomy defect reconstruction with pediculed latissimus dorsi flap.Postoperative assessment of the transplant was made according to clinical criteria and viability of the flap was assessed via laser Doppler flowmetry. Signs of microcirculation improved starting from day 5 postoperatively, and were almost equal with donor site microcirculation signs on day 14. A sufficiently large mass of the transplant allowed to create a thickening over the epiglottis, as well as to close the defect   in the oral cavity. The latissimus dorsi flap in the tongue reconstruction has a high potential: its use provides a relatively good quality of articulation, recovery of deglutition.